Nucleotide-Binding Oligomerization Domain-Like Receptor 3 Deficiency Attenuated Isoproterenol-Induced Cardiac Fibrosis via Reactive Oxygen Species/High Mobility Group Box 1 Protein Axis - Liu, Chen; Hu, Tongtong; Cai, Zhulan; Xie, Qingwen; Yuan, Yuan; Li, Ning; Xie, Saiyang; Yao, Qi; Zhao, Jinhua; Wu, Qing Qing; Tang, Qizhu (Frontiers in Cell and Developmental Biology, 2020)
Nucleotide-binding oligomerization domain (NOD)-like receptor 3 (NLRP3) is involved in fibrosis of multiple organs, such as kidney, liver, lung, et al. However, the role of NLRP3 in cardiac fibrosis is still controversial and remain unclear. The study aims to investigate the role of NLRP3 on cardiac fibrosis induced by isoproterenol (ISO). In vivo, NLRP3 knock out (KO) and wild-type (WT) mice were subcutaneous injected with ISO to induce cardiac fibrosis model. The results showed that NLRP3 deficiency alleviated the cardiac fibrosis and inflammation induced by ISO. In vitro, neonatal rat cardiomyocytes (NRVMs) and primary adult mouse cardiac fibroblasts (CFs) of NLRP3 KO and WT mice were isolated and challenged with ISO. Adenovirus (Ad-) NLRP3 and si NLRP3 were used to transfect NRVMs to overexpress or knock down NLRP3. We found that NLRP3 could regulate high mobility group box 1 protein (HMGB1) secretion via reactive oxygen species (ROS) production in NRVMs and the HMGB1 secreted by NRVMs promoted the activation and proliferation of CFs. Thus, we concluded that NLRP3/ROS/HMGB1 pathway could be the underlying mechanism of ISO induced cardiac fibrosis.